Nurses’ Knowledge Regarding Incontinence-Associated Dermatitis - Asiri S; Alzahrani NS; Alharbi HF; Ayoub MY (Dove Medical Press, 2024)
Saeed Asiri,1 Naif S Alzahrani,2 Hanan F Alharbi,3 Mohammad Yahya Ayoub4 1Department of Nursing Administration and Education, College of Nursing, King Saud University, Riyadh, Saudi Arabia; 2Department of Medical-Surgical Nursing, College of Nursing, Taibah University, Medina, Saudi Arabia; 3Department of Maternity and Pediatric Nursing, College of Nursing, Princess Nourah Bint Abdulrahman University, Riyadh, 11671, Saudi Arabia; 4Department of Corporate Nursing Operations, Dr. Sulaiman Al Habib Medical Group, Riyadh, Saudi ArabiaCorrespondence: Saeed Asiri, Nursing Administration and Education Department, College of Nursing, King Saud University, Riyadh, Saudi Arabia, Email Saasiri@ksu.edu.saBackground and Objective: Incontinence-associated dermatitis (IAD), is a skin injury brought on by protracted exposure to urine or feces in the gluteal, sacral, or perianal regions. Therefore, this study aimed to evaluate nurses' level of knowledge, attitudes, social pressure, and intention to prevent IAD and to explore the factors that explain nurses' intention to prevent incontinence-associated dermatitis.Methods: A cross-sectional study was conducted among staff nurses from two designated hospitals in Riyadh, Saudi Arabia. The Knowledge, Attitudes, and Practices of the Incontinence-associated Dermatitis Questionnaire with 22 items (KAP-IAD-Q) on a five-agreement rating scale (1=not agreeable to 5=highly agreeable) was used. Also, the intention to use deep vein thrombosis (DVT) preventive measures was rated on a seven-point Likert scale, ranging from 1=strongly disagree to 7=strongly agree.Results: The participants showed that they had a sufficient knowledge (M= 48.2 ± 9.9) and, a positive attitude toward IAD prevention average score of 6.6 (SD ± 9.9) related to IAD etiology and risk factors. The perceived behavior to prevent IAD average was 5.1 (SD ± 3.9), showing that nurses had confidence and control in preventing IAD. The intention average score was 5.3 (SD ± 3.1), which indicates that nurses had the intention to prevent IAD. Furthermore, knowledge, attitude, social pressure, and perceived behavior to prevent IAD had a positive strong association with intention to prevent IAD (r= 0.547, p < 0.01; r= 0.564, p < 0.01; r= 0.579, p < 0.01; and r = 0.709, p < 0.01) respectively.Conclusion: The study highlights the critical role of knowledge, attitudes, social pressure, and perceived behavior in shaping nurses' intentions to prevent IAD. The findings demonstrate that nurses generally have a positive attitude and strong intention to prevent IAD, influenced by their level of education, hospital type, and clinical experience.Keywords: knowledge, attitude, practice, dermatitis, nurses, Saudi Arabia